The effect of a supportive educational intervention developed based on the Orem's self‐care theory on the self‐care ability of patients with myocardial infarction: a randomised controlled trial. Issue 11 (16th April 2015) - Mohammadpour, Ali; Rahmati Sharghi, Narjes; Khosravan, Shahla; Alami, Ali; Akhond, Majid
<x xml:space="preserve">Abstract</x> Aims and objectives The aim of this study was to assess the effect of a supportive educational intervention developed based on the Orem's self‐care theory on the self‐care ability of patients with myocardial infarction. Background Patients with cardiovascular disease suffer from the lack of knowledge about the disease and consequently are not able to fulfil their own self‐care needs. Design This was a randomised controlled trial conducted in 2012. Methods We recruited a random sample of 66 patients with myocardial infarction who had been recently discharged from coronary care unit. The study setting was two university hospitals located in Khorasan, Iran. Patients were randomly allocated to either the experimental or the control groups. Patients in the experimental group received education, support, and counselling while patients in the control group received no intervention. We employed a demographic questionnaire and the Myocardial Infarction Self‐Care Ability Questionnaire for data collection and spss version 16.00 for data analysis. Findings After the study, patients in the experimental group had higher levels of self‐care knowledge, motivation and skills compared to the prestudy readings and the control group. Conclusion The supportive educational intervention developed based on the Orem's self‐care theory can improve nonhospitalised patients' self‐care ability and positively affect public health outcomes. Consequently, using the developed programme for providing follow‐up care to nonhospitalised patients is recommended. Relevance to clinical practice Having the ability to develop caring systems based on the nursing theories is a prerequisite to standard nursing practice. Identifying patients' educational needs is a fundamental prerequisite to patient education. Our findings revealed that the supportive educational intervention developed based on the Orem's self‐care theory can help health care providers identify and fulfil patients' self‐care needs.